PERUBAHAN PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP KEPEMIMPINAN JOKO WIDODO MENGENAI PERMASALAHAN HUKUM DAN HAK ASASI MANUSIA TAHUN 2014-2016 - Simon Satria Simangunsong; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is grounded by a government that is trying to revise the weakening Corruption Eradication Commission law as well as past human rights cases that have been promised to be resolved as soon as possible but to date have not found a bright spot. Leadership Joko Widodo seemed to forget his promise Campaign and Nawa Cita in the field of Law and Human Rights. The formulation of the problem in this research is "How is the perception of University of Riau Students toward the leadership of Joko Widodo in terms of policy of handling Law and Human Rights?".The research approach used is quantitative approach. While the type of research used is a comparative causal study. Data collected by the author using observation, questionnaire / questionnaire, and documentation. The data used are primary data obtained from the research respondents and then supported by secondary data obtained indirectly from the object of research.The result of the research shows that the perception of students of the University of Riau on law enforcement and human rights during the leadership of Joko Widodo, is in good category on 100 days of service because the leadership of Joko Widodo has promised Indonesian people to uphold the law of justice and solve the problem Human rights both past and present. However, the students' perceptions change after 100 days of work so that the category is less good because many cases of law enforcement that is one-sided and solving the problems of Human Rights both in the present and in the past are not assertive even tended to be considered playful by the authorities .Keywords: Perception, University of Riau Students, Leadership, Law and Human Rights